Leadership succeeding in the private, public, and not-for-profit sectors - Sims, Ronald R.; Quatro, Scott A. 1968- (M.E. Sharpe, 2004)
Whether in the for-profit, not-for-profit, or government sector, organizations today face tough new challenges posed by changing global and domestic environments using diverse workforces. Leaders have to practice different styles appropriate to more complex and dynamic situations than ever before